Overcoming dormancy in seeds of biribá and seedling growth - Coutinho, Pablo Wenderson Ribeiro; Villa, Fabíola; Pires, Ely; Siqueira, Hingrit Mazurek (Scientia Agraria Paranaensis, 2018)
The study aimed to evaluate the influence of overcoming dormancy of seeds of biribá through chemical and mechanical method in the emergence and initial growth of seedlings. The fruits were acquired from a mother plant in Cascavel (PR). The experimental design was a completely randomized in factorial 2 x 3, with four repetition, containing 25 seeds each repetition. The first factor was constituted of scarification with sandpaper n.80 of the two sides opposite the micropyle (with and without), the second factor was the soaking for 24 h (water, GA3 in the concentration of 1000 mg L-1 and without soaking). The count was performed for up to 60 days, being calculated the emergence speed index, average time of emergence and speed of emergence. When the stabilization was achieved, the ratings of seedlings as the main root length and shoot, diameter of stem, number of leaflets, dry biomass of root, shoot and total seedlings. The imbibition in GA3 promoted to overcome dormancy leishmaniasis, being that the chiseling in conjunction obtained better average speed of emergence and seedling length, thus confirming that the two techniques in conjunction assists in the growth of biribá seedlings.